2009
DOI: 10.1172/jci37430
|View full text |Cite
|
Sign up to set email alerts
|

The natriuretic peptide/guanylyl cyclase–A system functions as a stress-responsive regulator of angiogenesis in mice

Abstract: Cardiac atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) modulate blood pressure and volume by activation of the receptor guanylyl cyclase-A (GC-A) and subsequent intracellular cGMP formation.Here we report what we believe to be a novel function of these peptides as paracrine regulators of vascular regeneration. In mice with systemic deletion of the GC-A gene, vascular regeneration in response to critical hind limb ischemia was severely impaired. Similar attenuation of ischemic angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
75
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 49 publications
(84 reference statements)
2
75
2
Order By: Relevance
“…35 Furthermore, in a pressure overload-induced hypertrophy model, selective disruption of the endothelial GC-A shows diminished angiogenesis. 34 Our present results extend these studies by identifying BNP for the first time as a coronary angiogenic factor. BNP is among the earliest cardiac factors induced in response to hemodynamic load, 6 and this mechanical stretch-induced activation of BNP gene expression is mediated by GATA.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…35 Furthermore, in a pressure overload-induced hypertrophy model, selective disruption of the endothelial GC-A shows diminished angiogenesis. 34 Our present results extend these studies by identifying BNP for the first time as a coronary angiogenic factor. BNP is among the earliest cardiac factors induced in response to hemodynamic load, 6 and this mechanical stretch-induced activation of BNP gene expression is mediated by GATA.…”
supporting
confidence: 85%
“…39,40 Interestingly, the effects of NPs are not mediated by the endothelial release of VEGF-A and autocrine/paracrine activation of the VEGF receptor in vitro in endothelial cell cultures. 34 Our results demonstrate that BNP gene delivery significantly improved LV systolic function after infarction, suggesting that the enhancement of BNP function selectively in the heart may be a potential new therapy after MI. Because growing evidence indicates that the loss of functional capil- laries and microvessels is a critical determinant of myocardial remodeling, 41 we investigated whether BNP has an impact on myocardial angiogenesis.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The difference in the inhibitory responses between ODQ and DT-3, although it was modest, may be derived from the existence and function of a natriuretic peptides/receptorlinked GC pathway, which is another cGMP/PKG-activating pathway. 3,29 Numerous studies have revealed that circulating EPCs mobilized from BM significantly contribute to angiogenesis in ischemic tissue. 8 Although the mobilization of EPCs from BM is a complex mechanism, it has been suggested that both eNOS expression and local secretion of metalloproteinase-9, a downstream activator of NO, in BM are essential for the mobilization of EPCs.…”
Section: Discussionmentioning
confidence: 99%